Biosignal processing methods to explore the effects of side-dominance on patterns of bi- and unilateral standing stability in healthy young adults - Négyesi, János; Petró, Bálint; Salman, Diane Nabil; Khandoker, Ahsan; Katona, Péter; Wang, Ziheng; Almaazmi, Anfal Ibrahim Sanqour Qambar; Hortobágyi, Tibor; Váczi, Márk; Rácz, Kristóf; Pálya, Zsófia; Grand, László; et al. (Frontiers in Physiology, 2022)
We examined the effects of side-dominance on the laterality of standing stability using ground reaction force, motion capture (MoCap), and EMG data in healthy young adults. We recruited participants with strong right (n = 15) and left (n = 9) hand and leg dominance (side-dominance). They stood on one or two legs on a pair of synchronized force platforms for 50 seconds with 60 seconds rest between three randomized stance trials. In addition to 23 CoP-related variables, we also computed six MoCap variables representing each lower-limb joint motion time series. Moreover, 39 time- and frequency-domain features of EMG data from five muscles in three muscle groups were analyzed. Data from the multitude of biosignals converged and revealed concordant patterns: no differences occurred between left- and right-side dominant participants in kinetic, kinematic, or EMG outcomes during bipedal stance. Regarding single leg stance, larger knee but lower ankle joint kinematic values appeared in left vs. right-sided participants during non-dominant stance. Left- vs. right-sided participants also had lower medial gastrocnemius EMG activation during non-dominant stance. While right-side dominant participants always produced larger values for kinematic data of ankle joint and medial gastrocnemius EMG activation during non-dominant vs. dominant unilateral stance, this pattern was the opposite for left-sided participants, showing larger values when standing on their dominant vs. non-dominant leg, i.e., participants had a more stable balance when standing on their right leg. Our results suggest that side-dominance affects biomechanical and neuromuscular control strategies during unilateral standing.